2019
DOI: 10.1111/vec.12898
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulse oximetry as a surrogate for PaO2in awake dogs breathing room air and anesthetized dogs on mechanical ventilation

Abstract: Objective:To evaluate the ability of arterial hemoglobin oxygen saturation measurement via pulse oximetry (SpO 2 ) to serve as a surrogate for PaO 2 in dogs.Design: Two-part study: prospective observational and retrospective components. Setting: University teaching hospital.Animals: Ninety-two dogs breathing room air prospectively enrolled on a convenience basis. Retrospective evaluation of 1,033 paired SpO 2 and PaO 2 measurements from 62 dogs on mechanical ventilation.Interventions: Dogs with concurrent SpO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
(81 reference statements)
0
25
0
Order By: Relevance
“…It should be emphasized that arterial blood gas analysis remains ideal for the assessment of oxygenation and to address the presence of hypoxemia [ 43 , 44 ]. In the present study, arterial blood gas analysis was not performed.…”
Section: Limitationsmentioning
confidence: 99%
“…It should be emphasized that arterial blood gas analysis remains ideal for the assessment of oxygenation and to address the presence of hypoxemia [ 43 , 44 ]. In the present study, arterial blood gas analysis was not performed.…”
Section: Limitationsmentioning
confidence: 99%
“…Oxygenation status was initially assessed with pulse oximetry during the respiratory crisis. Despite SpO 2 being associated with a low sensitivity for detection of hypoxaemia, it has reliability and an accuracy of ±2 per cent between saturations of 70 per cent and 100 per cent 30 31. In this case, the use of pulse oximetry was suitable as the patient had a rapid response to oxygen via face mask supplementation (100 per cent SpO 2 achieved).…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study SpO 2 , used in a single determination to estimate PaO 2 in dogs, showed a clinically low sensitivity (Farrell et al . 2019). However, although values of PaO 2 were not available, SpO 2 can still be considered a valid alternative, particularly for evaluating the response to treatment.…”
Section: Discussionmentioning
confidence: 99%